The effect of anabolic-androgenic hormones on postprandial triglyceridaemia and lipoprotein profiles in man - Hislop, Michael Stuart (MRC/UCT RU for Exercise and Sport Medicine, 2018)
It has been hypothesised that endogenous testosterone and AAS may predispose humans to premature CHD. However, there is no direct evidence to link these hormones with a greater prevalence of premature CHD. The aim of this thesis was to better describe atherosclerotic risk associated with these hormones by clarifying their effect on additional risk factors for premature atherosclerosis. Little is known about the effect of testosterone and AAS on 'atherogenic dyslipidaemia', a phenotype characterised by elevated postprandial triglyceridaemia, small dense LDL and a low HDLC concentration, which confers a high risk of CHD. Accordingly, the magnitude of postprandial triglyceridaemia, LDL and HDL particle size, and LDLC, HDLC and Lp(a) concentration were compared in male (n=9) and female (n=3) bodybuilders after self administration of AAS for 5-6 weeks (ON cycle) and again after a 4-6 week 'washout' period (OFF cycle), and in normal males (T) (n=10) before and during a reversible suppression of endogenous testosterone, induced using a GnRH agonist (triptorelin), and in a control group (C) (n=8). Lipoprotein size was assessed by gradient gel electrophoresis (GGE), lipoprotein concentrations by immuno and enzymatic assay, and postprandial triglyceridaemia by a standardised oral fat tolerance test (65g/m² ). HDLC decreased in male bodybuilders (0.94±0.30 vs 0.70±0.27 mmol/L, p=0.004; x ± SD) and female bodybuilders (1.3±0.5 vs 0.8±0.2 mmol/L) ON cycle. GGE studies suggested that mostly HDL₂ was reduced. There were no significant reductions in LDL particle size ON cycle. Two males had larger LDL species ON cycle. Lp(a) decreased in male bodybuilders (124.7±128.0 to 69.3±73.3 U/L, p=0.008). ON cycle postprandial triglyceride excursion was unchanged in female bodybuilders and reduced (11.6±10.0 vs 7.5±5.4 mmol/L.hr; p=0.027) in male bodybuilders. In the triptorelin study, HDLC was increased in T (1.07±0.18 vs 1.41±0.28 mmol/L, p=0.002) and not in C. GGE studies indicated an increase of HDL₂ in five T subjects and no increase in C. Total cholesterol increased in T (4.77±0.80 vs 5.24±1.04 mmol/L, p=0.039) but not in C. LDL size increased in four T subjects, and not in C. Lp(a) increased in T (277.9±149.l vs 376.5±222.2 U/L, p=0.004), but not in C. Postprandial triglyceridaemia was unchanged in both T and C. The results of these studies did not show any additional atherogenic effects of endogenous testosterone or AAS in humans. Rather, a suppression of Lp(a) may be an antiatherogenic effect of these hormones. A reduced postprandial triglyceridaemia and increased LDL size in individuals who are predisposed to 'atherogenic dyslipidaemia', may be further antiatherogenic effects of AAS use.